The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae) - Liston, Andrew; Prous, Marko; Vårdal, Hege (Zootaxa, 2019)
Six valid species of Pseudodineura are now recognised as occurring in the West Palaearctic, and the only described species of the related genus Endophytus. Larvae of all species are leaf-miners in Ranunculaceae. An identification key to adults is provided, followed by species commentaries which include summarised data on taxonomy, larval host plants, and distribution, with particular reference to Sweden. Whereas identification of some specimens using morphological characters may not be possible, each species apparently has a distinct COI barcode sequence. Pseudodineura heringi (Enslin, 1921) is a new junior synonym of P. parvula (Klug, 1816). Pseudodineura mocsaryi Zombori, 1976 and P. scaligera Zombori, 1979 are new junior synonyms of P. clematidisrectae Hering, 1935. Lectotypes are designated for: Dolerus minutus Hartig, 1837, Pelmatopus clematidis Hering, 1932, P. enslini Hering, 1923, P. heringi Enslin, 1921, and P. mentiens var. konowi Enslin, 1921.